Religious Expression of Urban Muslim Youth in Surakarta: The Da'wa of Bikers Iqro Community - Abraham Zakky Zulhazmi (Fakultas Dakwah dan Ilmu Komunikasi, 2024)
This research aims to analyze the Islamic preaching activities of urban Muslim youth in Surakarta, specifically the Bikers Iqro community. The religious expressions of urban Muslim communities, often distinct from traditional Muslim groups, are perceived as a form of commodification of Islam. One example of such modern and pop-culture-infused religious expression can be observed in the Bikers Iqro community in Surakarta. This study adopts a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The findings reveal that the Bikers Iqro community blends religious devotion with youth culture. They regularly organize forums for religious learning and preaching while simultaneously pursuing their hobbies, such as riding motorcycles together and customizing their bikes. Most members of the community are beginners in understanding religion. Their preaching themes focus on light and fundamental topics related to the basics of Islam.